Handbook of Nanotechnology in Nutraceuticals - Ahmed, Shakeel (CRC Press, Taylor & Francis Group, 2023)
Nanotechnology has been emerging as an important tool in the nutraceutical and food industries to improve the overall quality of life. Nanotechnology has established a new horizon by bestowing modified properties on nanomaterials and applying them to the production of nanoformulations, nutritional supplements, and the food industry. The Handbook of Nanotechnology in Nutraceuticals highlights the impact of nanotechnology on the food industries.The book focuses on the application of nanotechnology in nutraceuticals and the food industry to improve the overall quality of life. The book also addresses some important applications of nano-nutraceuticals in the treatment of different diseases, such as oxidative stress, cancer, neurodegenerative disorders, cardiovascular diseases, and so on.Features• Presents a scientometric approach to analyze the emergence of nano-nutraceuticals in cancer prevention and treatment• Examines various strategies employed to prepare nanocarrier systems, such as nanoparticles, nanostructure lipids, phospholipid-based nanocarriers, polysaccharide-based nanostructures, and metal nanoparticles• Discusses various regulatory issues related to nanotechnology and their application in different fieldsThis book is a valuable reference for nanotechnologists, scientists, and researchers working in the field of food technology, food science, pharmaceuticals, and nutraceuticals
Keywords: bicssc / Food & beverage technology